Soil bacterial community structure, metabolic adaptations, and their functional interactions to abiotic factors in Antarctica - Jani, Kunal; Mahajan, Anoop; Kajale, Swapnil; Ashar, Aditee; Sharma, Avinash (Polish Polar Research, 2021)
Antarctica features one of the most ancient, largest glacier reserves and the most pristine environment left on the earth. However, in the last few decades disturbances due to industrialization and release of greenhouse gases have led to serious consequences such as melting of polar ice sheets, changing atmospheric chemistry and ozone depletion. Here, we use high-throughput sequencing to understand the impact of subtle changes in environmental parameters on bacterial communities. We observed dominance of Cyanobacteria (41.93%) followed by Bacteroidetes (14.8%), Acidobacteria (13.35%), Proteobacteria (9.67%), Actinobacteria (7.79%), Firmicutes (3.46%) among all the samples collected every alternate day for 20 days. Additionally, metagenomic imputations revealed a higher abundance of gene families associated with DNA repair and carotenoid biosynthesis enabling bacterial communities to resist and function under the high UV radiations. We further observed bacterial communities are dependent on the single carbon metabolism as a strategy for nutrient uptake in such nutrient deprived conditions.